Essays on alternative work arrangements - Ganserer, Angelika (2021)
This dissertation consists of three essays which study alternative work arrangements in various forms and different contexts. The essays cover a range of alternative work arrangements, namely contracting out, temporary agency work, and solo self-employment. In addition, the essays discuss different drivers, side-effects, and compliance issues related to the use of alternative work arrangements.
Keywords: Graue Literatur; Hochschulschrift